The Black Dahlia - Cohen, Rudy.; Diamant, Moshe; Linson, Art.; Friedman, Josh.; De Palma, Brian; Hartnett, Josh, 1978-; Johansson, Scarlett, 1984-; Eckhart, Aaron; Swank, Hilary; Zsigmond, Vilmos; Isham, Mark.; Ellroy, James, 1948-; et al. (Universal City, Calif. : Universal Pictures, 2006)
Set in 1940s Los Angeles. Two police officers, Bucky Bleichert and his partner, Lee Blanchard, investigate the death of Elizabeth Short - also known as The Black Dahlia, a young woman who is found brutally murdered with a corpse so mutilated, the photos are kept from the public.
Widescreen.
Based on the novel by James Ellroy.
Special features: "Reality and fiction: the story of 'The Black Dahlia" ; the case file ; the De Palma touch.
DVD release of the 2006 motion picture.
Director of photography, Vilmos Zsigmond ; editor, Bill Pankow ; music, Mark Isham ; costume desiger, Jenny Beavan ; production designer, Dante Ferretti.
Josh Hartnett, Scarlett Johansson, Aaron Eckhart, Hilary Swank, Mia Kirshner, Mike Starr, Fiona Shaw, Patrick Fischler, James Otis.
Keywords: Short, Elizabeth, -- 1924-1947 -- Drama; Police -- California -- Los Angeles -- Drama; Murder -- Investigation -- California -- Los Angeles -- Drama; Mutilation -- Drama; Man-woman relationships -- California -- Los Angeles -- Drama; Feature films; Films for the hearing impaired